Confidential patent application with an example of preparation - Čabarkapa, Obrad T.; Petrović, Dalibor P.; Bojović, Milan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
In order that the invention solving a technical problem receives a patent protection, it is necessary to file a patent application. For the protection of confidential inventions which are important for defense and national security, a confidential patent application[1] must be filed. A confidential patent application is an important and complex document, the parts of which are, in principle, exposed in an established order. For the preparation of patent applications, it is necessary to engage experts with higher education, primarily in the technical field the invention relates to. The contents of the patent application is a basis for examining whether the application meets the requirements for patentability and whether the right to patent protection is achieved. Besides theoretical discussions on patent application, the paper gives a short version of an example of an application regarding a protected confidential invention. Introduction The basic condition for the exercise of patent protection is filing a patent application, the test procedure and, eventually, depending on the test results - the recognition or rejection of the patent. The paper gives a description of all parts of the patent application on an example of a confidential invention already patented. The content of the confidential patent application The confidential patent application for confidential invention protection consists of the following parts: The application for a patent; description of the invention; the claims (indication of what is new and what is required to be protected by patenting); abstract (short summary of the invention) and a draft of the invention (to which the description and the claims are referred). The application for a patent The application for patent is filed on Form P-1 and a request for the petty patent on Form MP-1. The data entered in the file is, for example: the applicant; the lawyer; the name of the invention in Serbian and English; the inventor; the rest of the patent application, etc.. Description of the invention The description of the invention aims to provide sufficient technical data and to further clarify and describe all the details of the invention for which protection is sought in the claims. The description should enable the average expert in the specific field of technology to perform or to conduct a procedure on the application and determine whether it meets the requirements for patentability. The description contains the following units: title of the invention; technology field; technical problem; state of technology; brief summary of the invention; a brief description of the figures of the draft; detailed invention description and the methods of industrial and other applications of the invention. The claims The claims are the most important part of the patent application and all other elements of the patent application are in a function of patent claims. The claims must define the invention solely by its technical characteristics. They are submitted on a separate sheet after the description of the invention under the title "The claims". Depending on the protection sought, one or more claims can be placed. Abstract The abstract contains the title of the invention and a brief summary of the invention as shown in the description, the requirements and the draft. A brief review must indicate the technical field to which the invention relates and must allow a clear understanding of the technical problem, the essence of the problem and the basic way (ways) of using the invention. The abstract contains a maximum of 150 words. Draft of the invention A draft of the invention is submitted on separate sheets, along with the title of the invention on each side. The reference signs given in the description, requirements and the draft must be the same throughout the application. Other documents with the patent application In addition to the above mentioned sections of the patent application, the following is submitted: power of attorney; cofirmation on presenting the invention at an international exhibition; certified copy of the first patent application; statement on the basis of entitlement to file an application; statement by the inventor if he does not want to be mentioned in the patent application; proof of the payment of the patent application fee; statement of a joint representative if there are more applicants. Conclusion In order that a confidential invention receive patent or petty patent protection, it is necessary to file a patent application. A confidential patent application is a very comprehensive document which has to be compiled with expert knowledge from both the technical field to which the application relates and the field of intellectual property protection. The shown content of the confidential patent application with an example can be useful for inventors in their attempts to draw up their own patent applications. [1] The structure and the content of a confidential patent application is identical to the content and the form of a patent application submitted to the Intellectual Property Office,a competent state institution for the protection of intellectual property.